2020
DOI: 10.1136/jech-2020-214676
|View full text |Cite|
|
Sign up to set email alerts
|

Association of socioeconomic deprivation with opioid prescribing in primary care in England: a spatial analysis

Abstract: BackgroundThe increasing trends in opioid prescribing and opioid-related deaths in England are concerning. A greater understanding of the association of deprivation with opioid prescribing is needed to guide policy responses and interventions.MethodsThe 2018/2019 English national primary care prescribing data were analysed spatially. Prescribing of opioids in general practice was quantified by defined daily doses (DDD) and attributed to 32 844 lower layer super output areas (LSOAs), the geographical units repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“… 7 More than 231 million opioid prescriptions were dispensed in primary care in 2018–2019 alone. 8 Research also shows a variation in prescribing patterns across geographical locations and socioeconomic factors. The majority of the highest prescribing areas are located in the North of England and deprivation is strongly associated with opioid prescribing when accounting for population demographics and disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“… 7 More than 231 million opioid prescriptions were dispensed in primary care in 2018–2019 alone. 8 Research also shows a variation in prescribing patterns across geographical locations and socioeconomic factors. The majority of the highest prescribing areas are located in the North of England and deprivation is strongly associated with opioid prescribing when accounting for population demographics and disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in the plethora of research that studies spatial aspects of health in different ways, for example, as spatial patterns of diseases and mortality (e.g. Marshall 1991, Lawson 2018, Kulldorff, Nagarwalla 1995, Santos et al 2020, Nowakowska et al 2021, geographical distribution of healthcare services and their utilization (e.g. Santana et al 2009, Gravelle et al 2014, Longo et al 2017, Okoli et al 2020, Shinjo, Aramaki 2012, Pongiglione et al 2020, Renner 2020), E1 E2 A. Renner, R. Santos, B. Pongiglione, R. Hoffmann or environmental shocks on population health (Gemmell et al 2000, Analitis et al 2008, Almendra et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed gender, age and socio-economic deprivation to be implicated for higher OMEQ doses of opioids (Spooner 2016;Todd et al 2018;Macfarlane et al 2020;Nowakowska et al 2020;Richards et al 2020). Studies…”
Section: Comparison Of Trends In Opioid Burdenmentioning
confidence: 96%
“…Added to this, concerns about rising rates of opioid prescribing in the UK have escalated since the start of the 2000's Ruscitto et al 2015). This is in part, a result of the highly publicised problems experienced in North America (Weisberg and Stannard 2013;Vokinger 2018;Verhamme and Bohnen 2019) again, concentrated in areas of greatest socioeconomic deprivation (Kurani et al 2020;Nowakowska et al 2020). Wales is a country where a sizeable part of the population have poor health (Public Health Wales Observatory 2018; StatsWales 2020; NHS Wales 2021) and live in relative poverty (Barnard 2018).…”
Section: Why Is Research Needed In Wales?mentioning
confidence: 99%
See 1 more Smart Citation